Напрями підвищення якості людського капіталу в аграрній сфері - Вініченко, Ігор Іванович; Vinichenko, Igor; Лапа, Вероніка Олегівна; Lapa, Veronica (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2019)
У статті розглянуто підходи до підвищення якості людського капіталу в аграрній сфері. Проаналізовано сучасL ний стан та особливості використання персоналу сільськогосп одарських підприємств в умовах кризи. Вивчено сутність формування кадрового потенціалу агропідприємств, що забезпечує отримання конкурентних переваг на ринку за рахунок ефективної кадрової стратегії. Наведено основні напрями підвищення якості персоналу сільськогосподарсьL ких підприємств у кризових умовах. Зауважено на проведенні оцінки людського капіталу за рахунок розвитку та навчання працівників. Розглянуто економічний зміст відтворення людського капіталу в аграрній сфері, що грунтується на стадіях формування, розподілу або обміну та використання. Визначено окремі дестабілізуючі чинники, що впливають на якість людського капіталу в системі відтворення сільськогосподарського виробництва. ЗапропоноL вано напрями вдосконалення відтворювального процесу якісного людського капіталу в аграрній сфері шляхом ствоL рення регіонального єдиного аграрного освітнього простору, що є стратегічним завданням щодо формування та виL користання персоналу в аграрній сфері. The article considers approaches to improving the quality of human capital in the agrarian sector. The current state and peculiarities of the use of staff of agricultural enterprises in the conditions of crisis are analyzed. The essence of forming of personnel potential of agro enterprises is studied, which provides obtaining competitive advantages in the market at the expense of the developed effective personnel strategy. The main directions of improving the quality of the personnel of agricultural enterprises are given, namely: organization of continuous training of employees; optimal selection and placement of personnel; formation of corporate spirit of the enterprise; creation of preconditions and factors of career growth; stimulation of the constant orientation of em ployees to professional development. The basic measures for improving the use of the personnel of agricultural enterprises by providing the necessary educational qualification level of personnel, formation and improvement of the system of motivation of labor, ensuring functioning of the system of estimation of results of work, social protection of workers, implementation of measures for raising the level of innovation orientation of work, implementation of measures for protection, is substantiated. labor and raising the level of work capacity, ensuring the system of raising the educational and qualification level through staff development programs. It was noted on the evaluation of human capital of agricultural enterprises in order to improve its quality through the development and training of employees. The economic content of reproduction of human capital in the agrarian sector, based on the stages of formation,distribution or exchange and use, is considered. Certain destabilizing and motivational factors that influence the quality of human capital in the system of reproduction of agricultural production are determined. The directions of perfection of the reproductive process of qualitative human capital in the agrarian sphere are proposed by creating a regional single agricultural educational space, which is a strategic task for the formation and use of personnel in the agrarian sector in crisis conditions of management.
Direction for in creasing the quality of human capital in agrarian sphere
І. І. Вініченко ORCID ID :0000L0002L9527L1625 ; В. О. Лапа ORCID ID: 0000L0002L5488L509X
Keywords: людський капітал; human capital; кадровий потенціал; human resources; персонал; staff; якість; quality; аграрна сфера; agrarian sector; сільськогосподарські підприємства; agricultural enterprises; відтворення; reproduction